Development of Transport as a Factor of the Economic Miracle (Wirtschaftswunder) of West Germany - Myszczyszyn, Janusz (Studia Historiae Oeconomicae, 2021)
In addition to the introduction, the article consists of three parts and conclusions. The broadest one includes the description of the assumptions and stages of the research procedure and its results, both on the empirical and methodological level. It is based on synthetic theoretical foundations presented on the basis of a review of international literature on the subject and review of the essence of the German economic miracle and the main trends in changes in the field of economic growth and transport development in Germany after World War II. The research presented in this way fits into the principles of the new economic history paradigm, which is still not very popular in Europe.